Effect Of The Husband Alert Journal (Jursiga) On Reducing Anxiety In Pregnant Women At Risk - Wulandara, Qanita; Bayu Irianti; Uly Artha Silalahi (Media Informasi, 2025)
Pregnancy is a critical period in a woman's life, often accompanied by physical and psychological changes that may lead to anxiety. Anxiety during pregnancy, particularly in high-risk cases, can negatively impact both maternal and fetal health. This study aims to assess the effect of the Husband Alert Journal (Jursiga) in reducing anxiety levels among pregnant women at risk. This pre-experimental study involved 33 pregnant women in their third trimester, with mild to severe anxiety. A non-equivalent one-group design with pre-test and post-test was used. The results showed a significant reduction in anxiety levels, with the majority of participants reporting mild anxiety after using the journal (63.63%), compared to severe anxiety before the intervention (63.63%). Statistical analysis using a Paired Samples Test revealed a significance value (p) of 0.000, indicating that the use of Jursiga was effective in reducing maternal anxiety. The study highlights the importance of involving husbands in the maternal care process and suggests that providing support through the Jursiga journal can be an effective intervention for reducing anxiety in pregnant women at risk.